Image quality and radiation dose comparison in medium and high kilovoltage for digital PA chest radiography - Moey, Soo Foon; Muhd Jaafar, Nur Farah Hani; Saidin, Nursyahirah (Kulliyyah of Allied Health Sciences, IIUM, 2019)
Introduction: Various medium and high tube potentials were utilized to conduct chest x-rays. There are advantages and disadvantages with regards to image quality and radiation dose when using medium and high kilovoltage (kVp) technique. However, radiographers have misconstrued understanding pertaining to the choice of tube potential as well as grid usage when performing chest radiography. Methods: The experimental study was conducted using the PBU-50 phantom by exposing it with medium kVp utilizing grid and non-grid as well as high kVp with grid. All images obtained were evaluated using the modified evaluation criteria for PA chest established by the Commission of European Communities, 1996 whilst the dose area product (DAP) was determined using the Dose Area Product (DAP) meter. The value obtained from the DAP meter was converted to entrance surface dose (ESD) using CALDOSE_X5.0 software and mathematical formula. Results: The Wilcoxon Signed-Rank Test indicated a significant difference in ESD when using medium and high kVp; Z= -2.666, p <0.05. Additionally, a significant difference in ESD was also indicated when using medium kVp with and without the grid; Z= -2.201, p <0.05. Further, Wilcoxon Signed-ranked Test indicated that there was a significant difference in image quality when using medium and high kVp; Z= -2.666, p< 0.05. Conclusions: Medium kVp should be used to demonstrate pathological conditions as well structures composed of calcium like the rib, spine or calcified lesions. Otherwise, high kVp is the preferred choice due to its low radiation dose and overall image quality acceptability.